Evolução do estado nutricional de pacientes com pancreatite crônica alcoólica em aconselhamento dietético ambulatorial - Beninca, Simone Carla [UNIFESP] (2017)
Introduction: Chronic alcoholic pancreatitis can lead to changes in nutritional status. Objectives: To evaluate and describe the evolution of the nutritional status of patients with chronic alcoholic pancreatitis secondary to dietary counseling during outpatient follow-up, using anthropometry and electrical bioimpedance methods; Secondarily, to analyze whether the presence of diabetes, the use of enzyme replacement therapy and the presence of cachexia influenced the nutritional status of patients during outpatient follow-up, and also to identify calorie and macronutrient dietary changes during outpatient follow-up in response to counseling Nutritional dietary. Patients and methods: A prospective, longitudinal study was carried out from March 2010 to March 2016. The nutritional status was evaluated through anthropometry and electrical bioimpedance. And the food intake in a quantitative way was evaluated by means of the average intake by the 24 hour food recall (Rec 24h) and the usual food day (DAH). For each variable studied, the relevant statistical test was applied. Results: A total of 44 patients were evaluated, 37 of whom remained in the study until the end of the study, which averaged 4.45 ± 1.28 years. The disease duration at the first visit was 7.51 ± 7.10 years, 45.5% of the patients had associated diabetes, and 75% used enzyme replacement therapy. Of the patients studied, 45.5% presented cachexia due to the loss of> 5% of the weight in the last 6 months. In relation to the classification of nutritional status, small changes were verified with the passage of time, both in the parameters that evaluate fat as in lean mass. When verifying the evolution of the nutritional status by different anthropometric parameters, no significant alteration was verified. When patients were separated by presence or absence of cachexia, diabetes and enzyme use, no significant changes in nutritional status were also observed over time. When evaluating the evolution of food intake it was verified that the caloric intake is adequate to the needs, and that the lipid intake had a significant reduction with the passage of time. Conclusion: Dietary counseling maintained the nutritional status of patients with chronic pancreatitis unchanged over the years. The presence of diabetes, the use of enzyme replacement therapy and the presence of cachexia did not negatively influence nutritional status over the years. Most of the patients were found to be eutrophic or with some degree of malnutrition, and still had variations in the amount of body fat. Intake of calories and macronutrients remained adequate, but with nutritional counseling there was a reduction in lipid intake, necessary for patients with chronic pancreatitis.